Effects of Dietary Energy Density in a Fermented Total Mixed Ration Formulated with Different Ratios of Rice Straw and Cassava Pulp on 2- or 14-Day-Aged Meat Quality, Collagen, Fatty Acids, and Ribonucleotides of Native Thai Cattle Longissimus Muscle - Chanporn Chaosap; Achara Lukkananukool; Sineenart Polyorach; K. Sommart; Panneepa Sivapirunthep; Rutcharin Limsupavanich (Foods, 2022)
This study investigated the effects of dietary energy density in rice straw and cassava pulp fermented total mixed ration on pH, cooking loss, Warner−Bratzler shear force (WBSF), and collagen content of 2- or 14-d-aged native Thai cattle (NTC) Longissimus thoracic (LT) muscles and fatty acids and ribonucleotides of 2-d-aged LT. Eighteen yearling NTC (Bos indicus) were randomly divided into three dietary treatments (T1 = 8.9, T2 = 9.7, and T3 = 10.5 MJ ME/kg), with six bulls per treatment. The results showed that T1 had the highest WBSF (p < 0.05). However, T2 had similar WBSF to T3 (p > 0.05). With aging, cooking loss increased (p < 0.01), while WBSF decreased (p < 0.01). Insoluble and total collagen decreased with aging (p < 0.05). Dietary energy density had no effect (p > 0.05) on collagen content, ribonucleotides and most fatty acids. However, T1 had more (p < 0.05) decanoic (C10:0), vaccenic (C18:1n9t), trans-linolelaidic (C18:2n6t), eicosatrienoic (C20:3n6), and docosadienoic (C22:2) acids than T2 and T3. In terms of lowest feed cost with comparable tenderness to T2 and highest energy density, T3 may be well suited for feeding NTC. Aging for 14 days improves LT tenderness, but its cooking loss may affect yield and juiciness.
Keywords: Meat and Animal Product Quality; Animal Nutrition and Physiology; Protein Hydrolysis and Bioactive Peptides